Vibration reduction optimization of the mistuned bladed disk considering the prestress. (January 2019) - Zhang, Hongyuan; Yuan, Huiqun; Yang, Wenjun; Zhao, Tianyu
Ignoring the effect of prestress can increase the gap between the actual results and research results, which is not conducive to improve the vibration localization of bladed disk system and the finite element calculation. To improve the vibration localization and computational efficiency, the prestressed component mode synthesis method (PCMSM) was adopted to establish the finite element reduced-order model considering prepress. Since the main calculation precision of the prestressed component mode synthesis method was the mode truncation number, calculation was made to the eigenfrequency of different mode truncations; the contrast and analysis were made to the calculation result of blisk model, minimum mode truncation number under the above calculation precision was obtained, and freedom of the model was greatly reduced. The finite element reduced-order model was collocated to make an analysis of the vibration response characteristics of mistuned bladed disk. From the aforementioned analysis, the maximum amplitude of mistuned bladed disk was not only associated with the mistuning value of blade but also related to the frequency of adjacent blade; on the basis of such a rule, the finite element reduced-order model was adopted to raise an optimization algorithm for the blade vibration reduction and arrangement. Results have revealed that the optimization algorithm has made an adequate consideration of both model precision and calculation speed. The maximum dimensionless amplitude of blade vibration under three mistuning patterns and upon optimization is greatly reduced by 32.8%, 30.1%, and 28%. The localization factor of blade vibration under three mistuning patterns and upon optimization is greatly reduced by 64%, 68.5%, and 57.2%. The optimization algorithm based on the prestressed component mode synthesis method gets the optimization value by not more than 15 iterations. The optimization algorithm has greatly reduced the amplitude of the blade and obviously dampened vibration localization of the bladed disk system.